Recruitmet Management of Prospective University Students through Non SNMPTN System at Teuku Umar University - Rizwan, Rizwan; Yusrizal, Yusrizal; Niswanto, Niswanto (Jurnal Pendidikan Progresif, 2021)
The purpose of this research is to find out: 1) planning of student recruitment by non SNMPTN (annual state university entrance test) system at the Teuku Umar University of Meulaboh. 2) The implementation of student recruitment by non-SNMPTN system at the Teuku Umar University of Meulaboh. 3) Supervision of student recruitment by non-SNMPTN system at the Teuku Umar University of Meulaboh. 4) Evaluation of student recruitment by non-SNMPTN system at the Teuku Umar University of Meulaboh. This research is using the descriptive method with qualitative approach. The data collection technique is by observation, interview, and documentation study. The subjects of the research are (1) Rector of Teuku Umar University of Meulaboh, (2) Vice Rector II, (3) Head of Bureau of Academic Affairs, Student Affairs, Planning, and Cooperation, (4) Head of Student Affairs Division. The result of the research shows that: 1) Planning, implementation, supervision, and evaluation of student recruitment by non-SNMPTN system at the Teuku Umar University of Meulaboh surely had several drawbacks in handling information systems.Keywords: recruitment management, prospective students, university entrance test.DOI: http://dx.doi.org/10.23960/jpp.v11.i3.202117